2024
DOI: 10.1007/s11696-024-03328-2
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the extracts and fractions of Dendranthema zawadskii and quantitative analysis of phenolic compounds by HPLC/UV

Jeong So,
Hak-Dong Lee,
Sullim Lee
et al.

Abstract: Dendranthema spp. are good sources of phenolic compounds with pharmacological effects. To improve industrial material e ciency and economic feasibility, Dendranthema zawadskii (DZ) was fractionated, and its functional substances and biological activities were evaluated. The linarin contents in the butanol (Bu) and ethyl acetate (EtOAc) fractions were 77.360 mg/g and 70.603 mg/g, respectively, which were approximately 3.4 times higher than those in the methanol extract. In the EtOAc fraction, the luteolin conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Another study reported that C. zawadskii var. lucidum flowers, containing high levels of 3- O -caffeoylquinic acid, 3,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid, and acacetin 7- O -rutinoside, exhibited skin-whitening activity by inhibiting melanin production in α-melanocyte-stimulating hormone-induced B16F10 cells [ 53 , 54 , 55 ]. The study also confirmed their antimicrobial activity against Staphylococcus aureus , Pseudomonas aeruginosa , and Candida albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that C. zawadskii var. lucidum flowers, containing high levels of 3- O -caffeoylquinic acid, 3,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid, and acacetin 7- O -rutinoside, exhibited skin-whitening activity by inhibiting melanin production in α-melanocyte-stimulating hormone-induced B16F10 cells [ 53 , 54 , 55 ]. The study also confirmed their antimicrobial activity against Staphylococcus aureus , Pseudomonas aeruginosa , and Candida albicans .…”
Section: Discussionmentioning
confidence: 99%